How tax avoidance and media exposure can increase CSR disclosure - Maya Aresteria; Alfita Rakhmayani; Deddy Sulestiyono; Alexandra Audrey Natali Ariadinata; Shesa Rizky Amalia (Proceeding International Conference on Accounting and Finance, 2026)
This research investigates the impact of media exposure and tax avoidance on the level of Corporate Social Responsibility (CSR) disclosure by companies. The study focuses on the food and beverage sector, sample of this study use 152 Financial reporting, particularly emphasizing the use of selected media platforms to ensure public acknowledgment of the company’s legal standing. The findings reveal that media exposure, specifically through corporate websites as a medium for publishing CSR activities, significantly influences the extent of CSR disclosure. Conversely, the analysis shows that tax avoidance does not have a significant effect on CSR disclosure levels.